Sexual Violence on University Campuses: Differences and Similarities in the Experiences of Students, Professors and Employees - Bergeron, Manon; Goyer, Marie-France; Hébert, Martine; Ricci, Sandrine (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2019)
This article presents a portrait of sexual violence on university campuses (SVUC) at six universities in Québec (Canada) and explores differences and similarities in the experiences of students, professors and employees. Data are drawn from the Enquête Sexualité, Sécurité et Interactions en Milieu Universitaire (ESSIMU). They reveal disturbing rates of SVUC among students (36.2%), professors (38.8%) and employees (38.7%). The results show that the hierarchical status of perpetrators was higher than that of victims for a significant proportion of professors (33%) and employees (50.7%). When asked about the type of assistance they would want in the event of SVUC, the majority of students, professors and employees affirmed they would want support during the reporting/complaint process, information about available recourse within the university to report the incident, and psychological support provided by a resource outside the university.